2014
DOI: 10.4103/0028-3886.141278
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell transformation sequence 2 is a potential biomarker of unfavorable survival in human gliomas

Abstract: ECT2 expression is positively correlated with WHO pathologic grading and unfavorable survival, suggesting that ECT2 may be a potential therapeutic candidate in human gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…It is well described in the literature that upregulation of ECT2 confers poor clinical outcome in many different types of tumors [14,15,[18][19][20]. However, a comprehensive investigation remains to evaluate the clinical significance and prognostic value of ECT2 in CRC specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well described in the literature that upregulation of ECT2 confers poor clinical outcome in many different types of tumors [14,15,[18][19][20]. However, a comprehensive investigation remains to evaluate the clinical significance and prognostic value of ECT2 in CRC specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Those characteristics of ECT2 indicate that the mislocalization to the cytoplasm may enhance ECT2 oncogenic potential. Indeed, overexpressed ECT2 is identified in many types of human malignancies, including pancreatic cancer [12], lung cancer [13], glioma [14,15], breast cancer [16], etc. And increased ECT2 activates several Rho-regulated signaling pathway, which ultimately contribute to malignant transformation [10].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 19 published articles with 21 studies enrolling 5,305 patients met the inclusion criteria for the meta-analysis [11,15,[19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41]. A flow diagram of the detailed literature selection process is displayed in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Indeed, growing evidence suggests that ECT2 is frequently overexpressed in various cancers and serves as an oncogene [15][16][17][18]. Moreover, numerous clinical studies have shown that high ECT2 expression is associated with adverse clinicopathological characteristics, such as poor tumour differentiation, larger tumour size, positive lymphatic metastasis, and advanced disease stage, and as well as an unfavourable prognosis in multiple type of cancers [11,15,[19][20][21][22][23][24][25], further suggesting that it is a promising prognostic biomarker in cancers. Nevertheless, these previous studies are limited by sample sizes or study methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) classification grades glioma between well differentiated low grade glioma, WHO grades I–II, and high grade anaplastic glioma and glioblastoma, WHO grades III and IV, respectively (5). A higher grade glioma is associated with poor prognosis and increased mortality (6). Therefore, revealing the detailed molecular mechanism and the diagnostic and prognostic markers of glioma is crucial for the prediction of clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%